Numerical simulation on the reflection characterisation and performance of a solar collector - a case study of UPM solar bowl - Ng, Khai Mun; Adam, Nor Mariah; Zakaria, Azmi (Universiti Putra Malaysia Press, 2012)

(untitled)
A numerical simulation of UPM Solar Bowl is presented in this paper. The numerical analysis considered a general model of solar bowl, which was divided into three modules:(a) reflection characterisation of the bowl, (b) solar flux density along the receiver, and (c) radiation contour mapping of the receiver. The governing equations are resolved in a segregated manner using Matlab programming environment. The influence of the tropical clear sky irradiance on the collector was numerically studied, whereas the collector performance in time domain was also quantified. Single reflection is a major element in thermal concentration. It was observed that solar flux density of collector substantially deteriorated during off solar noon hour, in which during 08:00 and 16:00 under clear sky of tropics, the percentage reduction of flux density is over 82% at all points of the receiver. The simulated radiation contour mapping of the receiver supports the finding. Other results of the UPM Solar Bowl simulation model are also shown and discussed.